Respon Fisiologis Tanaman Cabai Terhadap Cekaman Kekeringan Dan Pemberian Mulsa Organik - * Silvana (CV. SINAR HOWUHOWU, 2026)
This study aimed to analyze the physiological responses of chili plants (Capsicum annuum L.) to drought stress and the application of various types of organic mulch. The research was conducted in a greenhouse at the Faculty of Agriculture, University of Northern Sumatra, from May to September 2025, using a completely randomized design (CRD) with two factors: drought levels (100%, 75%, and 50% of field capacity) and organic mulch types (no mulch, rice straw, dry leaves, and sawdust). The observed parameters included chlorophyll content, stomatal conductance, leaf water potential, photosynthetic rate, and proline accumulation. The results showed that drought stress significantly affected all physiological parameters of chili plants. The application of organic mulch, particularly rice straw, effectively reduced the negative effects of drought by maintaining soil moisture, lowering surface temperature, and enhancing water use efficiency. Plants treated with rice straw mulch exhibited the highest chlorophyll content and photosynthetic rate, while plants without mulch under severe drought conditions experienced the greatest decline. Increased proline accumulation under severe stress conditions indicated the activation of physiological adaptation mechanisms to water deficit. The interaction between drought levels and mulch types had a significant effect on leaf water potential and stomatal conductance. Overall, rice straw mulch under moderate drought conditions produced the most favorable physiological performance, with a leaf water potential of -1.20 MPa and a photosynthetic rate of 9.7 µmol CO₂ m⁻² s⁻¹. These findings suggest that organic mulch application is an effective strategy for mitigating drought stress and promoting sustainable agriculture in tropical dryland ecosystems.